Komponen Theory of Planned Behavior pada Perilaku Disfungsional Auditor BPK RI Perwakilan Bali - Savitri, Ni Made Karina Dwitya; Wirama, Dewa Gede (E-Jurnal Akuntansi, 2024)
This study seeks to analyze the elements of the theory of planned behavior (TPB) influence on the dysfunctional intentions and behavior among the auditors of The Audit Board of Indonesia (BPK RI) Representative of Bali Province. Data were collected from 60 auditors through purposive sampling technique using questionnaires. Data analyzed using linear regression analysis techniques with using SPSS software. The analysis results implied that auditors' permissive attitude towards dysfunctional behavior and perceived control in the form of ease of performing dysfunctional behavior have a positive influence on auditors' intention to engage in dysfunctional behavior. However, subjective norms have no influence on auditors' intention to engage in dysfunctional behavior. Furthermore, the intention to behave dysfunctionally has a positive effect on the dysfunctional behavior of BPK RI Representative of Bali Province auditors. Keywords: Theory of Planned Behavior; Attitude; Subjective Norm; Percieved Behavioral Control; Dysfunctional Audit Behavior